The investigation of re-enforcement depressurization process in high-pressure hoses - L. N. Yurtsev; A. V. Kurakin (Тонкие химические технологии, 2009)
The investigation of the process of de-pressurization in high-pressure hoses under the thermal aging conditions by the evaluation of the de-pressurization pressure in the places of the arrangement of drain holes has been conducted.